Modern Doctoral Education in Russia: Current Directions of Development - Boris I. Bednyi; Evgeny V. Chuprunov (Высшее образование в России)
The article is based on the materials of the report presented at the plenary session of the Professors’ Forum 2019 “Science. Education. Regions” of the All-Russian Public Organization “Russian Professorial Assembly” (Moscow, Peoples’ Friendship University of Russia, February 6, 2019). In the context of the problems that were discussed at the Forum, three points have been formulated, which, according to the authors, determine the priority areas in the development of modern Russian doctoral education: 1. Doctoral education and dissertation. Since the institution of doctoral education is the main resource for training professional researchers and university teachers, postgraduate programs should be aimed at the defense of PhD (Candidate of Sciences) theses. 2. The educational component of postgraduate programs. Doctoral education should be developed as a research program that includes an educational component, rather than as an educational program that includes a research component. 3. Training of research personnel for the regions. In the context when budgetary resources for supporting doctoral education are concentrated in the country’s leading universities, the problem of reproducing highly qualified personnel at regional universities, which do not have such a status, is of particular relevance. The article proposes some specific measures to improve the national system for training of highly qualified personnel in postgraduate schools.